Perennial Ryegrass Yield Performance under Abiotic Stress. Issue 4 (15th June 2017) - Kemesyte, Vilma; Statkeviciute, Grazina; Brazauskas, Gintaras
Abstract : Breeding of perennial ryegrass ( Lolium perenne L.) for forage is mainly aimed at increase in herbage yield. However, abiotic stresses such as drought and winterkill threaten persistence and ability to produce stable aerial biomass of the plant. Field experiments, performed under natural conditions, rather than dissection of abiotic stress factors under artificial or semiartificial conditions, offers opportunity to evaluate the effect of complex of abiotic stresses on the plant performance. The aim of this study was to evaluate the relationship between dry matter yield and tolerance to winter kill and drought of perennial ryegrass ecotypes and cultivars differing in their ploidy level during a 2‐yr period. The field experiment was located in Akademija, Lithuania (55°40′ N, 23°87′ E) in 2015 and 2016. The germplasm consisted of 128 diploid and 25 tetraploid perennial ryegrass populations. Winterkill, spring growth and regrowth after cuts, drought damage, and dry matter yield were assessed. Short periods of lower than −10°C temperatures with slim snow cover determined low damages of the perennial ryegrass after winters. Medium correlation was estimated between drought damages and dry matter yield. Tetraploid genotypes of perennial ryegrass demonstrated higher tolerance to cold and drought stress conditions, better spring growth and regrowth after cuts, and higher dry matter yield.